Biodiversity conservation, advocacy coalitions, and science-focused disputes: the case of Caymanian coral reef conservation and the proposed port expansion project - Bailey, Sabine; Morris, Daniel; Dunning, Kelly (Frontiers in Marine Science, 2023)
An environmental dispute arose in the Cayman Islands where politicians and multinational cruise companies sought an infrastructure upgrade that would destroy 15 acres of coral reef habitat. A competing coalition emerged to contest this project resulting in important policy change: the first ever people’s-initiated referendum. Our research uses the Advocacy Coalition Framework (ACF) to study how policy change is enacted in a biodiversity conservation policy system. We find differences between two coalitions in members, policy beliefs, resources, and strategy. Policy beliefs of both coalitions reveal two competing realities, especially on the subject of science needed to inform a sustainable tourism economy, with scientific misinformation becoming increasingly impactful in policy making. Second, we find that one coalition leveraged the interests of powerful politicians and international corporations to advocate for the infrastructure project, even though the destruction of coral reefs was in defiance of laws. To contest this, the second coalition leveraged volunteers and small donations to enact policy change, successfully triggering the referendum. Our research is significant because in places where volunteering and small donations are less possible, such as in emerging market economies, it is easy to see how well-resourced interests could degrade biodiversity even with domestic laws protecting species and habitats.